2017
DOI: 10.1039/c7ra01868a
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a co-culture cell micropattern model to simulate lung cancer bone metastasis for anti-cancer drug evaluation

Abstract: A549/OB co-culture micropattern was fabricated through μ-eraser strategy to mimic lung cancer bone metastasis for DOX efficacy evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…On the aligned samples, cells obtained an elongated morphology, aligned to the micropattern and mainly located on the microstrips (Figure S2, Supporting Information; Figure a). The empty space between the microstrips may facilitate cell migration and proliferation . A significantly greater number of cells was measured after 7 d of seeding (Figure S3, Supporting Information), indicating the peptide/silica micropattern did not compromise hMSC proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the aligned samples, cells obtained an elongated morphology, aligned to the micropattern and mainly located on the microstrips (Figure S2, Supporting Information; Figure a). The empty space between the microstrips may facilitate cell migration and proliferation . A significantly greater number of cells was measured after 7 d of seeding (Figure S3, Supporting Information), indicating the peptide/silica micropattern did not compromise hMSC proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Aligned micropattern cues are crucial for cell proliferation, migration, and differentiation, and also result in the secretion and deposition of anistropic extracellular matrix (ECM) specific to tissue types . Our recent work on hMSC differentiation in silicified silk/R5 composites demonstrated that this composite material promoted osteogenic differentiation of hMSCs in an osteoinductive environment in vitro, as compared to the silk plain controls .…”
Section: Resultsmentioning
confidence: 99%
“…The micropattern platform creates multi-organ co-culture in a single compartment with different organ cells spatially separated using cell micropatterning techniques (Figure 2A (c)). [66] Different types of cells are often selectively attached to or removed from 2D culture substrate with regional (patterned) surface modification that tunes cell attachment, [67,68] or encapsulated in different hydrogels patterned in 3D configuration. [69] Different organ cell interactions are mainly mediated by diffusion through the overlying medium, and sometimes also by physical contact with neighboring cells.…”
Section: Advances In Multi-organ Integration Platformsmentioning
confidence: 99%
“…Yet although such experiments are common on tissue and groups of cells embedded in synthetic matrices, they are rarely performed on individual cells in vitro. Batch processes that apply force to populations of cells, whether in 3D matrices or in monolayers [4]- [9], [12], [13], make it difficult to precisely control the loading conditions applied to each cell and to isolate the force response from other contributing factors. This isolation is crucial to investigating how mechanical deformation alone affects both suspended and adherent cells, which once understood can shed light on the role of more complicated interactions between cells and their surroundings when subjected to force.…”
Section: Introductionmentioning
confidence: 99%